Functional Divergence of G and Its Homologous Genes for Green Pigmentation in Soybean Seeds - Tokumitsu, Yusuke; Kozu, Takuto; Yamatani, Hiroshi; Ito, Takeshi; Nakano, Haruna; Hase, Ayaka; Sasada, Hiroki; Takada, Yoshitake; Kaga, Akito; Ishimoto, Masao; Kusaba, Makoto; Nakashima, Taiken; et al. (Frontiers in Plant Science, 2022)
The degradation of chlorophyll in mature soybean seeds is closely related to the development of their yellow color. In this study, we examined G, its homologue G-like (GL), and their mutant alleles and investigated the relationship between these genes and chlorophyll accumulation in the seed coats of mature seeds. Transient expression of G and GL proteins fused with green fluorescent protein revealed that both were localized in plastids. Overexpression of G resulted in the accumulation of chlorophyll in the seed coats and cotyledons of mature seeds, indicating that high expression levels of G result in chlorophyll accumulation that exceeds its metabolism in the seeds of yellow soybean. Analysis of near isogenic lines at the G locus demonstrated a significant difference in the chlorophyll content of the seed coats and cotyledons of mature seeds when G and mutant g alleles were expressed in the d1d2 stay-green genetic background, indicating that the G protein might repress the SGR-independent degradation of chlorophyll. We examined the distribution of mutant alleles at the G and GL loci among cultivated and wild soybean germplasm. The g allele was widely distributed in cultivated soybean germplasm, except for green seed coat soybean lines, all of which contained the G allele. The gl alleles were much fewer in number than the g alleles and were mainly distributed in the genetic resources of cultivated soybean from Japan. None of the landraces and breeding lines investigated in this study were observed to contain both the g and gl alleles. Therefore, in conclusion, the mutation of the G locus alone is essential for establishing yellow soybeans, which are major current soybean breeding lines.